Client Satisfaction Towards the Services of Lad Yao Hospital, Lad Yao District, Nahonsawan Province, Thailand - Tangmankingworakoon T. (2016)
A cross-sectional descriptive study was conducted on clients utilizing services of Lad yao hospital, Lad Yao district, Nakhonsawan province, Thailandl, in order to evaluate the client satisfaction of services of Lad Yao hospital in terms of promotive, preventive, curative and rehabilitative care, and identify the relationship between satisfaction towards the services and independent variables such as client,s expectation, attitude' and socio-demographic characteristics. In addition, a predictive factor for satisfaction and comments from the clients were also revealed in this study. Using a self-administered-questionnaire, data were derived from 898 clients utilizing hospital services, aged at least 18 years old during the period of data collection. Descriptive statistrcs was used to describe satisfaction level and independent variables while the relationships between these factors and client satisfaction were determined by correlation analysis and chi-scluare test. Logistic regression was further applied for predictive factor identification. Kruskal-wallis test was performed as an additional test for determinins the difference of satisfaction revels among the different reasons for visitation. The average score of client satisfaction was 3.9 andl only 52% of clients felt satisfled with the services. Regarding each aspect of care,there were 40%,50.g%and,84.6%of satisfied clients from the services of promotion-prevention, curative care and rehabilitation services, respectively. Age, educational level, the actual experience compared with the previous expectation, and attitude were fbund to be significantly associated with the satisfaction level. Attitude was identified as a predictive factor of satisfaction in all kind of health services' Moreover, it was revealed that among different reasons of visit, there was no significant difference of satisfaction level. A majority of comments from clients were based on inadequacy of staff and long waiting tin-res. Strategies emphasizing improving the irnage of the hospital should be continuously implemented since a good attitude could lead to higher satisfaction level. Satisfaction surveys and qualitative research in each service unit were suggested for further study to identify client satisfaction details.